2012
DOI: 10.1016/j.dental.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Are self-adhesive resin cements a valid alternative to conventional resin cements? A laboratory study of the long-term bond strength

Abstract: OBJECTIVES: The aim of the study was to test whether or not the shear bond strengths of six self-adhesive resin cements to dentin and to glass-ceramic, 24h and long-term-aged, are similar to the one of a conventional resin cement. METHODS: Human molars (N=168, n=12 per group) and silicabased glass-ceramic specimens (N=168, n=12 per group) were embedded in acrylic resin and randomly divided into 28 groups. The following resin cements were luted according to the manufacturers' instructions: Clearfil SA (CSA), G-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
105
1
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 24 publications
(36 reference statements)
5
105
1
18
Order By: Relevance
“…No entanto, de acordo com os estudos de outros autores, não se encontrou diferença de resistência de união em relação ao tipo de cimento utilizado (resinoso convencional ou autoadesivo) para a maioria dos tratamentos superficiais testados 6,18,19 . Porém, os resultados são muito variáveis, mostrandose, em alguns estudos, superiores 20,21 , e, em outros, inferiores, em relação aos cimentos resinosos convencionais 16,22 . Esta variação ocorre, provavelmente, pela diferença na composição dos agentes cimentantes e pela metodologia empregada.…”
Section: Discussionunclassified
“…No entanto, de acordo com os estudos de outros autores, não se encontrou diferença de resistência de união em relação ao tipo de cimento utilizado (resinoso convencional ou autoadesivo) para a maioria dos tratamentos superficiais testados 6,18,19 . Porém, os resultados são muito variáveis, mostrandose, em alguns estudos, superiores 20,21 , e, em outros, inferiores, em relação aos cimentos resinosos convencionais 16,22 . Esta variação ocorre, provavelmente, pela diferença na composição dos agentes cimentantes e pela metodologia empregada.…”
Section: Discussionunclassified
“…While some of the self-adhesive resin cements had similar values of bond strength to the conventional cement Panavia, others showed lower values before and after aging, in the long term 16 . Not all self-adhesive resin cements can be a valid alternative to conventional cement for binding silica based glass-ceramic to dentin 17 . Regarding the Multilink Sprint, although no statistical difference was showed for the two periods studied, there was a numerical increase in adhesive resistance after 1 year of storage.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion to dentin using contemporary bonding agents and selfadhesive resin cements seems to be more stable than previous generations of both types of these resin-based materials 9,[22][23][24] . This improvement is important for the durability of direct and indirect esthetic restorations, because research has shown that adhesive restorations become more reliable and predictable.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such advantages are not relevant if the resin cement does not perform adequately in terms of sealing and bonding. Studies have shown that bond strengths of some self-adhesive resin cements are lower than those of traditional resin cements [12][13][14][15][16][17][18][19][20][21][22][23] . On the other hand, resin coating could improve bond strength of conventional resin cements and its application may also potentially improve bond strength of self-adhesive resin cements to dentin.…”
Section: Introductionmentioning
confidence: 99%